TLR agonists as adjuvants for viral vaccines: mechanisms, applications, and future directions - Shao, Fengyan; Zhu, Xiangyu; Yi, Ming; Gao, Hongyu; Wu, Jiali; Fang, Ruikang; Xie, Yubiao; Han, Jicheng; Lu, Huijun (Frontiers in Microbiology, 2026)
Toll-like receptors (TLRs) play a pivotal role in the innate immune system by recognizing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), thereby initiating immune responses against viral infections. TLR agonists have emerged as promising adjuvants to enhance the efficacy of viral vaccines by modulating immune responses, improving antigen presentation, and promoting both humoral and cellular immunity. This review comprehensively summarizes the classification, signaling mechanisms, and immunomodulatory functions of cell-surface and intracellular TLRs. It further discusses the application of TLR agonists as adjuvants in vaccines against major viruses, including HBV, HCV, HIV, SARS-CoV-2, influenza, and flaviviruses. Key findings from preclinical and clinical studies highlight the potential of TLR agonists to overcome immune tolerance, enhance vaccine immunogenicity, and provide broad-spectrum protection. Finally, it points toward the “integration of precision adjuvants with novel vaccine platforms” as a core future direction, laying a theoretical and applied foundation for TLR agonists to become the next generation of viral vaccine adjuvants.